2019
DOI: 10.1186/s12967-019-1809-3
|View full text |Cite
|
Sign up to set email alerts
|

RIPK1 inhibition attenuates experimental autoimmune arthritis via suppression of osteoclastogenesis

Abstract: BackgroundRheumatoid arthritis (RA) is a chronic and systemic inflammatory disease characterized by upregulation of inflammatory cell death and osteoclastogenesis. Necrostatin (NST)-1s is a chemical inhibitor of receptor-interacting serine/threonine-protein kinase (RIPK)1, which plays a role in necroptosis.MethodsWe investigated whether NST-1s decreases inflammatory cell death and inflammatory responses in a mouse model of collagen-induced arthritis (CIA).ResultsNST-1s decreased the progression of CIA and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 32 publications
(43 reference statements)
3
22
0
1
Order By: Relevance
“…Bone erosion worsened in the placebo group over the study duration, with little change in the GSK2982772 group, but one patient in the GSK29822772 group, who showed a large improvement, may have contributed to much of the mean difference between treatment groups. Alternatively, this finding may support other studies that have suggested a potential role for RIPK1 inhibition in the suppression of osteoclastogenesis [ 22 , 44 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Bone erosion worsened in the placebo group over the study duration, with little change in the GSK2982772 group, but one patient in the GSK29822772 group, who showed a large improvement, may have contributed to much of the mean difference between treatment groups. Alternatively, this finding may support other studies that have suggested a potential role for RIPK1 inhibition in the suppression of osteoclastogenesis [ 22 , 44 ].…”
Section: Discussionsupporting
confidence: 87%
“…RIPK1-mediated necroptosis has also been implicated in increased cytokine production and inflammatory diseases [ 19 21 ]. Inhibition of RIPK1 blocked necroptosis, suppressed osteoclastogenesis, reduced synovial expression of proinflammatory cytokines, and decreased arthritis progression in a collagen-induced mouse model of RA [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The key regulators of necroptosis, RIPK1, RIPK3 and MLKL were potently increased in the synovium of a collagen-induced arthritis mouse model [83], indicating that necroptosis might be involved in the pathogenesis of RA. RIPK1 inhibitor Nec-1 significantly decreased the expression of these key regulators and suppressed the expression of IL-17, IL-1β, IL-6 and TNFα in the mouse model [84]. Therefore, inhibiting RIPK1 might be a novel therapeutic approach for the treatment of RA.…”
Section: Necroptosis In Rheumatoid Arthritismentioning
confidence: 98%
“…Cell death is an important driver of liver disease, while RIPKs were initially described as mediators of cell death and survival, emerging evidence indicates a necroptosis-independent role for the RIPKs in inflammation (9). Inhibition of RIPKs can decrease inflammatory response necroptotic cell death in vitro and in vivo (23). Oral RIPK1 inhibitor has been reported to be useful in inflammatory diseases, including psoriasis, inflammatory bowel disease, and rheumatoid arthritis (24,25).…”
Section: Discussionmentioning
confidence: 99%